HspB2/Myotonic Dystrophy Protein Kinase Binding Protein (MKBP) as a Novel Molecular Chaperone: Structural and Functional Aspects - Prabhu, Sankaralingam; Raman, Bakthisaran; Ramakrishna, Tangirala; Rao, Ch Mohan (PLOS ONE, 2012)
The small heat shock protein, human HspB2, also known as Myotonic Dystrophy Kinase Binding Protein (MKBP), specifically associates with and activates Myotonic Dystrophy Protein Kinase (DMPK), a serine/threonine protein kinase that plays an important role in maintaining muscle structure and function. The structure and function of HspB2 are not well understood. We have cloned and expressed the protein in E.coli and purified it to homogeneity. Far-UV circular dichroic spectrum of the recombinant HspB2 shows a β-sheet structure. Fluorescence spectroscopic studies show that the sole tryptophan residue at the 130th position is almost completely solvent-exposed. Bis-ANS binding shows that though HspB2 exhibits accessible hydrophobic surfaces, it is significantly less than that exhibited by another well characterized small HSP, αB-crystallin. Sedimentation velocity measurements show that the protein exhibits concentration-dependent oligomerization. Fluorescence resonance energy transfer study shows that HspB2 oligomers exchange subunits. Interestingly, HspB2 exhibits target protein-dependent chaperone-like activity: it exhibits significant chaperone-like activity towards dithiothreitol (DTT)-induced aggregation of insulin and heat-induced aggregation of alcohol dehydrogenase, but only partially prevents the heat-induced aggregation of citrate synthase, co-precipitating with the target protein. It also significantly prevents the ordered amyloid fibril formation of α-synuclein. Thus, our study, for the first time, provides biophysical characterization on the structural aspects of HspB2, and shows that it exhibits target protein-dependent chaperone-like activity.